Ответы и объяснения

Лучший Ответ!
2014-03-02T12:41:26+04:00
6    a)  (а²-b²)/16 : (b+a)/4=(a+b)(a-b)/16 * 4/(a+b)=(a-b)/4;
при а= 0.6, b=-0.2
(0.6-(-0.2))/4=(0.6+0.2)/4=0.8/4=0.2
      б)  (x²-2xy+y²)/4 : (5y-5x)/2=(x-y)²/4 * 2/(-5(x-y))=(x-y)/(-10)=(y-x)/10
при х=-2,  у=1
(-1-(-2))/10=(2-1)/10=0.1
7   a)   2^5/5 : 2^4/15=2^5/5 * 15/2^4=2 * 3=6
     б)   3^9/4 : 3^7:8=3^9/4 * 8/3^7=3² * 2=9 * 2=18
     в)   2^4/5³ : 2^6/5²=2^4/5³ * 5²/2^6=1/5 * 2²=1/5 * 4=1/20
8   a)   ab/3=6/3=2
     б)   а³b²/2 : a²b/8=a³b²/2 * 8/a²b=ab * 4=6 * 4=24
5   a)    5/(a²-2a) * (3a-6)/10=1/a(a-2) * 3(a-2)/2=1/a * 3/2=3/2a
     б)   (b²-1)/x * x²/(1+b)=(b-1)(b+1) * x/(b+1)=x(b-1)
     в)   (а+2)² * 5/(2+а)=5(а+2)
     г)   4/(2b+a) * (3a+6b)=4/(2b+a) * 3(a+2b)=4 * 3=12
7   a)   (b²-3b)/a^4 * a^4/(b²-9)=b(b-3)/(b-3)(b+3)=b/(b+3)
     б)   (4y-4x)/a^7 * a^8/(x-y)=-4(x-y)/1 * a/(x-y)=-4a
     в)   (m²-4n²)/2 * 6/(2n+m)=(m-2n)(m+2n)/1 * 3/(2n+m)=3(m-2n)
     г)   (a-2b)/x * x^4/(4b²-a²)=(a-2b)/1 * x³/(2b-a)(2b+a)= -x³/(2b+a)